Good profit how creating value for others built one of the world's most successful companies - Koch, Charles G. (New York Crown Business, 2015)
A Legendary CEO's Unique Management System In 1967, Charles Koch took the reins of his father's company and began the process of growing it from a
Includes bibliographical references and index.
Keywords: Management--Philosophy.